2022
DOI: 10.1111/tpj.15782
|View full text |Cite
|
Sign up to set email alerts
|

Insights into acylation mechanisms: co‐expression of serine carboxypeptidase‐like acyltransferases and their non‐catalytic companion paralogs

Abstract: SUMMARY Serine carboxypeptidase‐like acyltransferases (SCPL‐ATs) play a vital role in the diversification of plant metabolites. Galloylated flavan‐3‐ols highly accumulate in tea (Camellia sinensis), grape (Vitis vinifera), and persimmon (Diospyros kaki). To date, the biosynthetic mechanism of these compounds remains unknown. Herein, we report that two SCPL‐AT paralogs are involved in galloylation of flavan‐3‐ols: CsSCPL4, which contains the conserved catalytic triad S‐D‐H, and CsSCPL5, which has the alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Two of 3 CHI s ( chalcone isomerase ), 1 of 2 F3’H s, FNS ( flavone synthase ), 2 of 2 FLS s ( flavonol synthase ) were predominantly expressed in epidermis cells of 1 L and then 3 L (Figure 6b ). Transcription of three Serine carboxypeptidase‐like acyltransferases ( SCPLs ) were rich in 1 L tissues except epidermis cells (Yao et al ., 2022 ). In addition, there are other genes that are expressed cell‐specifically in 3 L, such as C4H ( CSS0005999 ) and ANR ( CSS0024761 ) (Figure 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of 3 CHI s ( chalcone isomerase ), 1 of 2 F3’H s, FNS ( flavone synthase ), 2 of 2 FLS s ( flavonol synthase ) were predominantly expressed in epidermis cells of 1 L and then 3 L (Figure 6b ). Transcription of three Serine carboxypeptidase‐like acyltransferases ( SCPLs ) were rich in 1 L tissues except epidermis cells (Yao et al ., 2022 ). In addition, there are other genes that are expressed cell‐specifically in 3 L, such as C4H ( CSS0005999 ) and ANR ( CSS0024761 ) (Figure 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…The pathway and key enzymes for galloylated and non-galloylated catechin biosynthesis in tea are well-understood based on recent studies ( Yao et al, 2022 , Dai et al, 2020 ; Cui et al, 2016b ; Jun, Lu, Docampo-Palacios, Wang, & Dixon, 2021 ). The non-galloylated catechins such as (–)–epicatechin, are synthesized from ( 2R , 3S , 4S )–leucocyanidin through three catalytic steps mediated by CsANS, CsANR, and CsLAR ( Jun, Lu, Docampo-Palacios, Wang, & Dixon, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The non-galloylated catechins such as (–)–epicatechin, are synthesized from ( 2R , 3S , 4S )–leucocyanidin through three catalytic steps mediated by CsANS, CsANR, and CsLAR ( Jun, Lu, Docampo-Palacios, Wang, & Dixon, 2021 ). The recent study showed that galloylated catechins ECG and EGCG are synthesized by CsSCPL4 and its non-catalytic paralog CsSCPL5, with the participation of β-glucogallin and non-galloylated catechins (–)–epicatechin or (–)–epigallocatechin ( Yao et al, 2022 ). It was surprising that the concentrations of non-galloylated catechins were higher in NB green teas, whereas galloylated catechins had a higher concentration in HJY green teas ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A PrimeScript RT kit was used to generate complementary DNA (cDNA) (Takara, Dalian, China). Table S3 presents the primer pairs for qRT-PCR, with the reference gene β-actin ( CSS0008920 ) . The manufacturer’s recommendations were followed during the thermal cycling.…”
Section: Methodsmentioning
confidence: 99%
“…Table S3 presents the primer pairs for qRT-PCR, with the reference gene β-actin (CSS0008920). 18 The manufacturer's recommendations were followed during the thermal cycling. Three independent biological replicates were guaranteed for each experiment.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%